Continuous signaling of CD79b and CD19 is required for the fitness of Burkitt lymphoma B cells. (18th April 2018) - He, Xiaocui; Kläsener, Kathrin; Iype, Joseena M; Becker, Martin; Maity, Palash C; Cavallari, Marco; Nielsen, Peter J; Yang, Jianying; Reth, Michael
Abstract: Expression of the B‐cell antigen receptor (BCR) is essential not only for the development but also for the maintenance of mature B cells. Similarly, many B‐cell lymphomas, including Burkitt lymphoma (BL), require continuous BCR signaling for their tumor growth. This growth is driven by immunoreceptor tyrosine‐based activation motif (ITAM) and PI3 kinase (PI3K) signaling. Here, we employ CRISPR/Cas9 to delete BCR and B‐cell co‐receptor genes in the human BL cell line Ramos. We find that Ramos B cells require the expression of the BCR signaling component Igβ (CD79b), and the co‐receptor CD19, for their fitness and competitive growth in culture. Furthermore, we show that in the absence of any other BCR component, Igβ can be expressed on the B‐cell surface, where it is found in close proximity to CD19 and signals in an ITAM‐dependent manner. These data suggest that Igβ and CD19 are part of an alternative B‐cell signaling module that use continuous ITAM/PI3K signaling to promote the survival of B lymphoma and normal B cells. Synopsis: The B‐cell antigen receptor (BCR) signaling component Igβ (CD79b) and the co‐receptor CD19 act as an alternative B‐cell signaling module that promotes the survival of B lymphoma and normal B cells via integrated ITAM/PI3K signaling. A new strategy for functional signaling studies of B‐cell lines by the CRISPR/Cas9 mediated deletion of BCR and B‐cell co‐receptor genes. The fitness of the human Burkitt lymphoma cell line Ramos requires the expression of the BCR signaling component Igβ and the co‐receptor CD19. Only Igβ but not Igα can be transported on the B‐cell surface in the absence of other BCR components. The BCR‐independent Igβ is found on the B‐cell surface in close proximity to CD19 and signals in an ITAM‐dependent manner. Abstract : The B‐cell antigen receptor (BCR) signaling component Igβ (CD79b) and the co‐receptor CD19 act as an alternative B‐cell signaling module that promotes the survival of B lymphoma and normal B cells via integrated ITAM/PI3K signaling.